Proposal of a Strategic Model that Shows the Essential Elements of Curricular Innovation - Urcid Puga, Rodrigo (2020)
In this article, a graphic proposal is made of the different elements that should be considered when thinking about curricular innovation within universities. This text aims to show the link that exists between some educational, social, cultural, economic variants, etc. that are linked in the subject when creating new educational approaches. The project carried out is presented through a qualitative methodology with the documented tool; it is conceived as a cross-sectional investigation in which the variables were not modified. The result of this project was a model that proves that curricular innovation cannot be approached from a single point or topic, but includes, series of concepts and interaction between them that should not be overlooked. This analysis only represents an approach of the many existing towards this topic and that some of the future studies may be the comparison between traditional and the most innovative ones, and even a series of quantitative studies that help to understand the correlation and / or existing relationship between teachers and students who choose to implement and accept curriculum innovation within the universities.